INFLUÊNCIA DA AMPLITUDE DE MOVIMENTO DE TORNOZELO NAS ALTERAÇÕES PROXIMAIS E DISTAIS NO TESTE STEP DOWN EM JOGADORES PROFISSIONAIS DE FUTEBOL (Movimenta (ISSN 1984-4298), 2021)
The objective was to demonstrate the correlation of kinematics of range of motion (ROM) of ankle dorsiflexion and of hips Internal Rotation with the dynamic changes of Lower Limbs during a Step Down Test (SDT). Materials and Methods: Participated of the study 30 professional soccer male athlets of Vila Nova Esporte Clube, who were avaluated for their functional aspects and motion standard by means of the ROM test of weight-bearing ankle dorsiflexion and the SDT. After collecting data, an statistical analysis was made using the Pearson’s correlation with the level of significance (p